Effects of carbon content on the photocatalytic activity of zinc oxide under visible light irradiation - Hussien, Nur Adilah (2019)
The research described in this thesis is an attempt to correlate structural and physicochemical properties of ZnO photocatalysts with their photocatalytic properties. ZnO photocatalysts were synthesized by sol-gel method from zinc acetate dihydrate (Zn(CH3COO)2.2H2O) in methanolic medium, either with or without the addition of cetyl-trimethyl ammonium bromide (CTAB) and sodium hydroxide. The ZnO powders synthesized with the addition of CTAB were calcined at 300, 400, 500, 600 and 700°C to produce ZnO that contained carbon. ZnO was also synthesized by a similar method without CTAB addition and calcined at 500°C. The structural and electronic properties of ZnO synthesized with the addition of CTAB (C-ZnO) and ZnO synthesized without the addition of CTAB (ZnO-500) were analysed. X-Ray diffraction pattern proved that the ZnO samples were crystalline hexagonal ZnO wurtzite with crystallite size range of 23-34 nm. Field emission scanning electron microscopic morphology of ZnO samples showed irregular-shape particles in the prepared C-ZnO and ZnO samples. Particle size of ZnO increased as the calcination temperature of ZnO was increased. The particle sizes of ZnO samples were distributed from 40 to 300 nm. The presence of carbon in ZnO samples after calcination was confirmed by Fourier transform infrared spectroscopy, thermogravimetric analysis and X-ray photoelectron spectroscopy. The photocatalytic oxidation of styrene in H2O2 catalyzed by ZnO photocatalysts was selective towards the production of styrene oxide. Among ZnO samples, ZnO-500 showed the highest selectivity towards styrene oxide which is 96.8%. This was explained by the presence of amorphous carbon in ZnO-500 indicated by the weight loss in thermogravimetric analysis which is due to the oxidation of amorphous carbon. The amorphous carbon caused the grey colour in ZnO-500, C-ZnO-300 and C-ZnO-400 due to aggregation of acetate during ZnO synthesis, and this was supported by C=C aromatic absorption peaks observed by Fourier transform infrared spectroscopy. White colour of C-ZnO-500, C-ZnO-600 and C-ZnO-700 was due to high content of organized carbon formed from the trapped acetate in CTAB during ZnO synthesis. Density functional theory (DFT) calculations were carried out to study the effects of carbon on the electronic properties of C-ZnO. The results showed lowest band gap energy caused by carbon substituted with oxygen.